Job Design and Employee Performance in Nigeria Bottling Company Plc, Benin City - ADAGBABIRI, Moses M.; ADAGBABIRI, Moses M.; OKOLIE, Ugo Chuks (Annals of Spiru Haret University. Economic Series, 2019)
Abstract Job design and employee performance are two concepts that are of significance to all modern corporate entities. A robust appreciation and application of these concepts will contribute in measurable respects to the growth and sustainability of various organizations. This study is an assessment of the impact of job design on employee performance in Nigerian bottling company plc, Benin City. A descriptive method was adopted and data was collected via a survey of 237 respondents. The study found that job design which comprises of job rotation, job enlargement and job enrichment has a positive correlation with employee performance. Requisite conclusion and recommendations were provided in the light of empirical and theoretical findings.